KNOWLEDGE ON HIV/AIDS AND STIGMA OF THE COMMUNITY TOWARD CHILDREN AFFECTED BY HIV/AIDS: RESEARCH CONDUCTED IN DISTRICT 8 AND BINHTHANH DISTRICT, HOCHIMINH CITY - Võ Hoàng Sơn (Tạp chí Khoa học Đại học Đà Lạt)
Using quantitative data from a research by the author titled "Stigma toward children affected by HIV/AIDS: A research conducted in District 8 and Binhthanh District, Hochiminh City", involving 200 people in the two Districts, the article analyses HIV/AIDS knowledge and stigma of the community toward children affected by HIV/AIDS. The results show that the accuracy of the people’s knowledge on HIV/AIDS is not high. There are still many misperceptions. People’s attitude towards children affected by HIV/AIDS is highly stigmatized, especially in situations where HIV/AIDS patients are their own children and grandchildren, the stigma is more apparent. The labelling of the community towards people living with HIV is quite heavy. However, prejudice and misperceptions about HIV do not affect people’s attitude. The results of the analysis show that gender, education, occupation, and lack of complete knowledge about HIV are factors that prevent the children affected by HIV from going to school together with other children.